Redefining Stagonomus Gorski based on morphological and molecular data (Pentatomidae: Eysarcorini) - Roca-Cusachs, Marcos; Jung, Sunghoon (Zootaxa, 2019)
After reconstructing the phylogenetic relationships among the closely related genera Carbula Stål, Eysarcoris Hahn, and Stagonomus Gorski (tribe Eysarcorini), using the mitochondrial genes: 16S rRNA and cytochrome oxidase subunit I (COI), and incorporating morphological characters to contrast our data, we transfer the species Eysarcoris gibbosus Jakovlev and Eysarcoris venustissimus (Schrank) to the genus Stagonomus, and we propose to place the subgenus Dalleria Mulsant & Rey as a synonym under the nominal subgenus Stagonomus. Additionally, Stagonomus is redefined to include diagnostic characters of the male genitalia.